Ribosome Hibernation as a Stress Response of Bacteria - Wang, Tianwen; Liang, Chen; Zheng, Mengyuan; Liu, Lu; An, Yafei; Xu, Hongju; Xiao, Sa; Nie, Lei (Protein and Peptide Letters, 2020)
Ribosome is primarily regarded as the committing organelle for the translation process. Besides the expansion of its function from a translational machine for protein synthesis to a regulatory platform for protein quality control, the activity regulation and recycling of ribosome have been deepened significantly. Recent advances have confirmed a novel mechanism in the regulation of ribosome activity when a cell encounters adverse conditions. Due to the binding of certain protein factors onto a ribosome, the structural and functional change of the ribosome inside the cell will take place, thereby leading to the formation of inactive ribosomes (70S monomer or 100S dimer), or ribosome hibernation. By ribosome hibernation, the overall protein synthesis rate of a cell could be slowed down. The resistance to adverse conditions or chemicals of the host cell will be enhanced. In this paper, we discussed the phenomenon, molecular mechanism, and physiological effect of ribosome hibernation when cells are under stresses. And then, we discussed the resuscitation of a hibernating ribosome and the role of ribosome hibernation in the treatment of antimicrobial infection.
Keywords: stress response